PENGARUH KOMPOSISI BIOPOTTING TERHADAP PERTUMBUHAN SEMAI SENGON (Paraserianthes falcataria (L) Nielsen) DI PERSEMAIAN BPDASHL KAHAYAN - Jerlina Kelly Purba; Wahyudi Wahyudi; Johanna M Rotinsulu (University of Lampung, 2022)
This study aims to determine the good biopotting composition for the growth of sengon seedlings and its resistance in nursery. This research was conducted at the BPDASHL Kahayan nursery and at the UPT Integrated Laboratory of the University of Palangka Raya. The research method used was Completely Randomized Design (CRD) with treatments: 30% clay + 70% peat soil (L1Gm1), 30% clay + 70% sawdust (L1Gr1), 30% clay + 70% dry compost (L1Kr1 ), 50% clay + 50% peat soil (L2Gm2), 50% clay + 50% sawdust (L2Gr2), 50% clay + 50% dry compost (L2Kr2) where each treatment was repeated by 10 times. The data collected and analyzed were the growth of sengon seedling height (cm), sengon seedling diameter (mm), sengon seedling quality index and the level of damage to biopotting. The results of this study indicate that the best treatment for height and diameter growth is composition of 30% clay + 70% dry compost (L1Kr1). This treatment also produces the best Seedling Quality Index. Meanwhile, the biopotting composition that produces the best resistance is 30% clay + 70% saw dust (L1Gr1).